PENGARUH MEDIA SOSIAL TERHADAP POPULARITAS DAN PERKEMBANGAN OLAHRAGA DIERA DIGITAL - Aidil Fauzan Matondang; Kristiando Simarmata; Ahmad Arif Sinambela; Jonatan Purba; Daramendra Ebed Tarigan; Edward Siburian; Fandi Ahmad Rambe; Muhamad Tarmizi; Ruth Ari Yanti Pasaribu; Yan Indra Siregar; Putra Arima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital media and information technology has brought about significant changes in the world of sports, including in the areas of communication, learning, promotion, and athlete performance improvement. This study aims to analyze the role of media and technology in supporting the development of sports in the digital age. The research methodology employed is a literature review, examining various relevant national and international journals on sports, digital media, and sports technology. The findings indicate that the use of social media, digital applications, wearable technology, video analysis, and online learning platforms has a positive impact on improving training quality, disseminating sports information, fostering interaction between athletes and the public, and enhancing the effectiveness of physical education. Additionally, technology plays a role in increasing public interest in sports activities through easily accessible digital content. However, several challenges remain, such as limited infrastructure, low digital literacy, and dependence on technology. Therefore, the wise and targeted use of technology is necessary to optimally support the development of sports in the modern era.